Ion cyclotron resonance for fast magnetosonic waves in small tokamaks - Pyatak, A.I.; Stepanov, K.N.; Borisko, S.V. (Вопросы атомной науки и техники, 2000)
The absorption of fast magnetosonic waves in a small-size tokamak has been studied under the multiple cyclotron resonance for bulk ions and under the fundamental resonance for minority ions. The small plasma radius is assumed to be less than or equal to, in the order of magnitude, the transverse wavelength. In this case, the solution to the linearized Vlasov equation for the distribution function of the resonance ions in the form of a power series in their Larmor radius and the expression for the contribution from resonance ions into the wave current density have been obtained. The nonlocal coupling between the wave field and current density in a small azimuth angle has been taken into account, which is associated with the motion of resonance ions along a magnetic line of force while travelling through the cyclotron resonance zone, with consideration for the nonuniform magnetic field along a line of force. Allowances have been also made for the decorrelation effects connected with the Coulomb collisions between the resonance particles during their travelling across the successive zones of the resonance, which effects lead to the dephasing of the particle-wave phase. The expressions for the RF power absorbed in the tokamak plasma have been obtained and analyzed.